The Urban Development in Relation to the Occurrence of Diseases in the Casa-Settat Region of Morocco during the Emergence of SARS-CoV-2. (9th August 2022) - Deblij, Sanaa; Bahlaouan, Bouchaib; Boutaleb, Nadia; Boutaleb, FatimaZahra; Bennani, Mohamed; El Antri, Said
Abstract : The Casa-Settat region is experiencing very worrying environmental and epidemiological problems and challenges, namely, population growth, the significant development of unsupervised industrial activities, road traffic, the significant weight of the spread of diseases with high epidemiological potential such as SARS-CoV-2, the increase in hospital activities, and the significant discharge of hospital effluents highly contaminated and untreated. To understand and analyze the factors influencing the high prevalence of deaths and the occurrence of diseases under surveillance, among others SARS-CoV-2, on the quantitative data recorded relating to ten regions of Morocco, and informing, on the one hand, on intrinsic data linked to the urban development, and on the other hand, on the evolution of diseases under epidemiological surveillance, a multidimensional analysis was made. The results reveal the typological framework highlighted by the factorial map F 1 × F 2 which showed the individualization of the region of Casablanca explained by a large number of variables and diseases that affect it. Finally, these results call for a diagnosis that will make it possible to model new approaches and implement new actions promoting the dynamics of environmental and epidemiological change in one of the most polluted and infected regions of Morocco.